2003
DOI: 10.1213/01.ane.0000055651.24073.59
|View full text |Cite
|
Sign up to set email alerts
|

Intrathecal Clonidine Added to a Bupivacaine-Morphine Spinal Anesthetic Improves Postoperative Analgesia for Total Knee Arthroplasty

Abstract: In this prospective, randomized, double-blinded, and placebo-controlled trial, we identify an effective postoperative analgesic approach in total knee replacement surgery. Intrathecal morphine (250 microg) combined with clonidine (25 or 75 microg) provided superior analgesia compared with intrathecal morphine alone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
42
0
7

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(50 citation statements)
references
References 15 publications
1
42
0
7
Order By: Relevance
“…Seven trials (9 comparisons) tested morphine 0.05 to 1 mg added to bupivacaine and reported on cumulative 24-h morphine consumption [4,30,38,41,56,61,74] (Supplemental Data 2). In controls, the median of the mean 24-h cumulative morphine consumption was 23 mg (range 4 to 47 mg).…”
Section: Cumulative 24-h Morphine Consumptionmentioning
confidence: 99%
See 1 more Smart Citation
“…Seven trials (9 comparisons) tested morphine 0.05 to 1 mg added to bupivacaine and reported on cumulative 24-h morphine consumption [4,30,38,41,56,61,74] (Supplemental Data 2). In controls, the median of the mean 24-h cumulative morphine consumption was 23 mg (range 4 to 47 mg).…”
Section: Cumulative 24-h Morphine Consumptionmentioning
confidence: 99%
“…Seventeen trials (21 comparisons) tested morphine 0.05 to 1 mg added to bupivacaine and reported on the incidence of postoperative pruritus [4,21,30,34,[37][38][39][41][42][43]46,56,61,69,74,75,79] (Table 2; Supplemental Data 6). The average incidence of pruritus with bupivacaine alone was 4.4%.…”
Section: Pruritusmentioning
confidence: 99%
“…We also found that the duration of analgesia was prolonged with the addition of clonidine when compared to that by neostigmine. The mechanism of action of clonidine is thought due to prolonging the motor blockade produced by local anaesthetic agents and also by bringing local vasoconstriction by acting on vascular smooth muscle (α-receptors), thereby decreasing the absorption of local anaesthetics from sub-arachnoid space leading to an increase in the duration of action [15,16]. According to Liu et al, neostigmine increases spinal levels of acetylcholine, thereby augmenting motor block [17].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, clonidine have synergistic action when used as adjuvant to local anesthetic resulting in postoperative analgesic requirement. (19,20) The use of dexmedetomidine, an alpha-2 agonist got FDA approval only for sedation in intensive care.…”
Section: Mechanism Of Actionmentioning
confidence: 99%